Avaliação fitoquímica, antioxidante e anti-inflamatória de Solanum corymbiflorum - Piana, Mariana (2017)
The plants have compounds that are related to different biological activities. Among these compounds, stand out the phenolic compounds which are capable of eliminate free radicals, and therefore, are involved in several reactions as reduction of the lipids and proteins oxidation. This way, these compounds are associated to prevention and treatment of various diseases related to inflammatory processes. The Solanum corymbiflorum, popularly known as baga-de-veado, is used in the folk medicine as anti-inflammatory and until the moment there are no studies related to this species. So, the aim of this study was quantify secondary metabolites, evaluate the antioxidant and anti-inflammatory activities of this species. In analysis by high performance liquid chromatography (HPLC) of the crude extract (CE) and fractions of the leaves, and fractions of the fruits observed the presence of caffeic acid, gallic acid, rutin and chlorogenic acid. This last was found in large quantity in the leaves CE and in the ethyl acetate (AcOEt) fraction of the fruits. Phenolic compounds, flavonoids, condensed tannins and alkaloids were quantified by spectrophotometry. For the leaves, the CE presented higher amounts of polyphenols, as well as better results related to antioxidant capacity by radical 2,2-diphenyl, 1-picrihidrazila (DPPH) inhibition. The chloroform fraction (CHCl3) of the leaves showed higher amount of alkaloids and better reduction of markers of oxidative stress (oxidation of the dichlorofluorescein diacetate–DCFH-DA and substances reactive to thiobarbituric acid–TBARS). The same results were found for the AcOEt and CHCl3 fractions of the fruits that presented higher amount of polyphenols and alkaloids, respectively. The CE of the leaves was used for evaluation of the anti-inflammatory activity after topical application of the irritating agent croton oil. This anti-inflammatory activity was verified through the measurement of ear edema (inhibition of 87±3%) and of the leukocyte infiltration evaluation, verified by enzyme myeloperoxidase activity (MPO) (reduction of 45±7%). Then, the leaves and fruits of S. corymbiflorum have pronounced antioxidant activity evaluated by different methods of oxidative stress and the leaves CE presented anti-edematogenic and antiinflammatory activities, proving the popular use of the species for the treatment of inflammatory skin diseases.